Estudio de factibilidad para la creación de una empresa productora y comercializadora de detergente liquido en el cantón Lago Agrio, provincia de Sucumbíos - Párraga Zambrano, Pascual Oswaldo (2017)
The main objective of this research work is to prepare a "FEASIBILITY STUDY FOR THE CREATION OF A PRODUCING AND MARKETING COMPANY OF LIQUID DETERGENT IN THE LAGO AGRIO CANTON, PROVINCE OF SUCUMBIOS." With the purpose of contributing to economic and competitive development. to be an essential instrument in any organization, which facilitates the effective commercialization of any type of product or service. The research that was applied to the families of the Lago Agrio canton corresponding to 119,930 inhabitants, value that was divided for 4 members of each family, for which it was considered to apply 395 surveys to the plaintiffs of the medium; as it was also applied to 82 suppliers of liquid detergent from the same canton for the purpose of determining the offer. It is very risky to try to make a company succeed without having previously prepared a feasibility study. For the development of the present investigation, the scientific, analytical - synthetic, inductive, deductive, statistical method and the observation and survey techniques were used. The results obtained in the market study were as follows: potential demand 26,584 families, actual demand 382,807 liters of liquid detergent in the first year an effective demand of 313,902 liters of liquid detergent, annual supply is 36,036 liters, unsatisfied demand Annual 277,866 liters of liquid detergent, in the technical study it was also determined that the installed capacity for the first year will be 230,400 liters of liquid detergent and that in the first year only 60% of the installed capacity will be used, thus offering 138,240 liters of liquid detergent. Regarding the financial study, it was determined that USD $ will be needed to invest in fixed assets. US $ 23,819.00; in deferred assets USD $. 4,139.91 US dollars, for one month of operation, USD $ is needed. 22,453.86 US dollars from the United States, giving a total investment of USD $. 50,412.77 United States dollars. In addition the price was obtained the sale price of USD $. 2.18 US dollars from the United States. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 90,466.90, which indicates that the project or investment is convenient. For the present project the IRR is 43.38%, this value being satisfactory to carry out the project, the time that would be required to recover the original investment would be 2 years, 3 months and 21 days, for the present project, the sensitivity values are less than one, therefore the changes in costs and revenues increased 8.93% and decreased by 7.77%, respectively, that is, the project is not sensitive to these changes. Later, the most significant conclusions and recommendations of the project are presented